The Adoption Act 1952 & the registration of Adoptions Act 1952: a study on the rights and procedures in adopting children in Malaysia / Liyana Shazzwanie Ismail, Nabilah Syahida Abdullah Salleh and Nur Azizi Wagini - Ismail, Liyana Shazzwanie; Abdullah Salleh, Nabilah Syahida; Wagini, Nur Azizi (2012)
Adoption is another way for a couple to have a child and it becomes an accepted norm by people all over the world. This project paper examines certain legal provisions governing adoption in Malaysia. There are still some issues that have not been dealt with clearly such as the child's welfare and rights, biological parent or parents' rights and consents, the court jurisdictions to hear the adoptions cases, the conditions and restrictions in granting the adoptions orders, the residency of both adopters and the child to be adopted and the issue of legitimacy of a child. We have found these issues by reading cases relating to adoption in Malaysia. The absence and ambiguity of certain provisions show that there are lacuna and room for improvement. The objectives of this research are to analyze the present law pertaining to adoption and its effectiveness in regulating the practice and also to propose a solution and reform certain provisions pertaining to adoption in Malaysia. The comparison is also made between the adoption law in United Kingdom and Singapore to find the similarities and differences between their adoption laws and Malaysia adoption law. The reasons why United Kingdom and Singapore was chosen are because Singapore has slightly similar provisions which are good for Malaysia to look into. While for United Kingdom, their statutes give more relevant provisions concerning to issues raised in Malaysia. Commentaries and recommendations are made in order to improve the existing law in our country.